A Large-Scale Investigation of Hypoxia-Preconditioned Allogeneic Mesenchymal Stem Cells for Myocardial Repair in Nonhuman Primates: Paracrine Activity Without Remuscularization. Issue 6 (18th March 2016) - Hu, Xinyang; Xu, Yinchuan; Zhong, Zhiwei; Wu, Yan; Zhao, Jing; Wang, Yingchao; Cheng, Haifeng; Kong, Minjian; Zhang, Fengjiang; Chen, Qi; Sun, Jianzhong; Li, Qian; et al.
Abstract : Rationale: : The effectiveness of transplanted bone marrow mesenchymal stem cells (MSCs) for cardiac repair has been limited; thus, strategies for optimizing stem-cell–based myocardial therapy are needed. Objective: : The present study was designed to test our central hypothesis that hypoxia-preconditioned MSCs (HP-MSCs) are more effective than MSCs cultured under ambient oxygen levels for the treatment of myocardial injury in a large-scale (N=49), long-term (9 months), nonhuman primate (Cynomolgous monkeys) investigation. Methods and Results: : MSCs were engineered to express green fluorescent protein, cultured under ambient oxygen or 0.5% oxygen (HP-MSCs) for 24 hours and then tested in the infarcted hearts of Cynomolgus monkeys (1×10 7 cells per heart). Hypoxia preconditioning increased the expression of several prosurvival/proangiogenic factors in cultured MSCs, and measurements of infarct size and left-ventricular function at day 90 after myocardial infarction were significantly more improved in monkeys treated with HP-MSCs than in monkeys treated with the control vehicle; functional improvements in normal cultured bone marrow mesenchymal stem cells–treated monkeys were not significant. HP-MSCs transplantation was also associated with increases in cardiomyocyte proliferation, vascular density, myocardial glucose uptake, and engraftment of the transplanted cells and with declines in endogenous cell apoptosis, but did not increase the occurrence of arrhythmogenic complications. Conclusions: : Hypoxia preconditioning improved the effectiveness of MSCs transplantation for the treatment of myocardial infarction in nonhuman primates without increasing the occurrence of arrhythmogenic complications, which suggests that future clinical trials of HP-MSCs transplantation are warranted. Abstract : Supplemental Digital Content is available in the text.